1988
DOI: 10.1111/j.1365-2842.1988.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of first primary palatine rugae to the maxillary canines in man

Abstract: Fifty dentate maxillary casts, obtained from thirty-four males and sixteen females, were mounted in the three-dimensional co-ordinate system of a contour meter. A transverse line of reference (x-axis) was drawn through the distal contact points of the maxillary canines, at a right angle to the y-axis which passed through the contact points of the maxillary central incisors. Relative to the canine-to-canine baseline, the locations of the lateral borders of the right and left first primary rugae were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…The supposed overall stability of palatal rugae suggest their use in surveying dentitional changes from year to year and preand post -treatment (25)(26)(27) . Controversy still exists a bout the stability of quantitative and qualitative characteristics of palatal rugae during growth (3,4,(28)(29) , orthodontic treatment with and without teeth extraction (30)(31)(32)(33)(34) , or as result of edentulism (19) .…”
Section: Introductionmentioning
confidence: 99%
“…The supposed overall stability of palatal rugae suggest their use in surveying dentitional changes from year to year and preand post -treatment (25)(26)(27) . Controversy still exists a bout the stability of quantitative and qualitative characteristics of palatal rugae during growth (3,4,(28)(29) , orthodontic treatment with and without teeth extraction (30)(31)(32)(33)(34) , or as result of edentulism (19) .…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also reported that the number of palatine rugae did not change greatly with age in younger adults (Kapali et al, 1977;Grove and Christensen, 1988;Shetty et al, 2005). It has been also shown that the transverse folds of the palatine mucosa do not significantly change after the use of orthodontic headgear or functional appliances (Almeida et al, 1995) or after transplantation of a free palatine graft (Breault et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
“…Cinquenta modelos em gesso de pacientes entre 12 a 52 anos foram avaliados quanto sua topografia por meio de um sistema coordenado tridimensional. O resultado do estudo constatou uma assimetria na topografia entre as primeiras rugas esquerdas e direitas, enquanto as demais foram consideradas simétricas (Grove & Christensen, 1988).…”
Section: Rugoscopia Palatina E a Mucosa Palatinaunclassified
“…Ao mesmo tempo, as medidas da espessura da mucosa diminuem de lateral para mediana e de região anterior para posterior (Marquezan et al, 2012). Ainda, a diferença de topografia pode ter influenciado no resultado por apresentar uma diferença na quantidade de tecido que compõem estas primeiras rugas palatinas (Grove & Christensen, 1988) No caso do deslocamento do ponto medial da primeira ruga esquerda, a tensão aplicada principalmente nessa região mais próxima ao local onde a abertura da sutura é maior, pode ter atingido um limiar que tornou a medida estatisticamente significante, resultando em um leve deslocamento da referida ruga. Já no caso das medidas transversais, a diferença de espessura compensou a abertura irregular do palato e confirmou um distanciamento proporcional das rugas palatinas.…”
Section: Análise Morfológica Das Rugas Palatinas Nos Tempos Estudadosunclassified